Antilarval substituted phenols, distribution of tricyclic pyrones in mice, and synthesis of unnatural amino acids - Nguyen, Thi D.T. (Kansas State University, 2014)
Three research projects were carried out and they are described below. The synthesis of substituted phenolic compounds including halogenated di- and trihydroxybenzenes, aminophenols, and substituted di-tert-butylphenols are described. Redox potentials of the synthesized molecules along with various known laccase substrates were measured, and an inverse relationship between the oxidation potential and the efficiency of oxidation by laccase of halogenated hydroxybenzenes and aminophenols is demonstrated. The synthesized substituted phenols were found to be substrates but not inhibitors of laccase. We discovered a new class of di-tert-butylphenols compounds that inhibits the growth of mosquito larvae at low concentrations. Compound 17, 2,4-di-tert-butyl-6-(3-methyl-2-butenyl) phenol caused greater than 98% mortality of third-instar larvae of Anopheles gambiae in the concentration of 0.18 µM. These compounds do not inhibit laccases. It appears that they affect a new target of the mosquito that is different from those of currently existing pesticides. Two anti-Alzheimer molecules, CP2 and TP70, discovered in our laboratory were studied for their pharmacokinetics and distribution. The distribution of CP2 and TP70 in mouse brain region and various tissues of mice were examined. HPLC analysis revealed that CP2 treatment in primary neurons accumulates in mitochondria fraction. Similarly, the amount of CP2 in the brain tissue from wild type and APP/PS1 mice treated with 25 mg/kg/daily for 2 months also have the highest concentration in the mitochondria fractions in the hippocampus. The results show that CP2 and TP70 can penetrate the blood brain barrier and accumulate in the tissue in significant amounts. Pharmacokinetics and bioavailability of compound TP70 were determined. Area under the curve and bioavailability value F were calculated, and data show that TP70 has a good PK profile and bioavailability. For the preparation of a novel tripeptidyl norovirus 3C-like protease (3CL[superscript]pro) inhibitor, the P3 unnatural amino acid, (S)-3-hydroxyphenylalanine was synthesized. The P3 is designed to increase the polarity with the addition of the alcohol group. After combining the P3 unnatural amino acid with the P1 and P2 to form the novel tripeptidyl compound, a study comparing the relations between the structure and its activity (SAR) will confirm whether prediction is correct in our pursuit for an antiviral therapeutic drug in the form of a protease inhibitor.
Keywords: Tricyclic pyrones; Antilarval substituted phenols; Unnatural amino acids; Anti-Alzheimer molecules; CP2 and TP70 in mouse brain region and tissues; Norovirus; Chemistry (0485); Chemistry, Pharmaceutical (0491); Organic Chemistry (0490)